Noninvasive vascular imaging of moyamoya: Diagnosis, followup, and surgical planning - Choudhri, Asim F.; Zaza, Aiad; Auschwitz, Tyler S.; Klimo, Paul; Mossa-Basha, Mahmud (Journal of Pediatric Neuroradiology, 2014)
Moyamoya disease and syndrome are typically described by their imaging features on cerebral angiography, however advances in noninvasive imaging has allowed improved anatomic and physiologic characterization of this vascular abnormality. Advanced imaging complements the role of cerebral angiography, and when used appropriately can provide valuable information regarding the diagnosis, treatment planning, and surveillance in patients with moyamoya. Techniques to be aware of include computed tomography, CT-angiography, Magnetic Resonance Imaging, MR Angiography (time-of-flight and dynamic contrast enhancemed angiography), and perfusion imaging (CT perfusion, arterial spin labeling perfusion, and nuclear medicine perfusion). With an appropriate understanding and implementation of noninvasive techniques, this disease process can be better understood allowing for improved patient management.
Keywords: Moyamoya; pediatrics; stroke; magnetic resonance imaging; perfusion; angiography